2012
DOI: 10.1016/j.clbc.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Administration of Zoledronic Acid Reduces Aromatase Inhibitor–Associated Bone Loss in Postmenopausal Women With Early Breast Cancer: 12-Month Analysis of the E-ZO-FAST Trial

Abstract: Aromatase inhibitors (AIs), an increasingly common adjuvant treatment option for postmenopausal women with hormone receptor-positive early breast cancer, are associated with bone loss that can impair patient quality of life. This study (E-ZO-FAST; Clinical Trials Identifier: NCT00171314) demonstrates that initiation of zoledronic acid therapy concurrent with adjuvant AI treatment improved skeletal health compared with zoledronic acid therapy initiated after deterioration of bone health. Background: Letrozole i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 35 publications
3
86
0
1
Order By: Relevance
“…In the Z-FAST study, 602 postmenopausal patients receiving adjuvant letrozole therapy were randomized to upfront vs. delayed zoledronate therapy (in the delayed group therapy was started if the BMD decreased to −2.0) [36]. In the companion studies ZO-FAST and E-ZO-FAST, similar results were found, despite the fact that the 3 studies included patients from different geographical areas [37,38]. In the ABCSG-12 trial, the BMD was studied in premenopausal women treated with goserelin and either tamoxifen or anastrozole, with or without zoledronate.…”
Section: The Prevention Of Adjuvant Breast Cancer Therapy-induced Bonsupporting
confidence: 61%
“…In the Z-FAST study, 602 postmenopausal patients receiving adjuvant letrozole therapy were randomized to upfront vs. delayed zoledronate therapy (in the delayed group therapy was started if the BMD decreased to −2.0) [36]. In the companion studies ZO-FAST and E-ZO-FAST, similar results were found, despite the fact that the 3 studies included patients from different geographical areas [37,38]. In the ABCSG-12 trial, the BMD was studied in premenopausal women treated with goserelin and either tamoxifen or anastrozole, with or without zoledronate.…”
Section: The Prevention Of Adjuvant Breast Cancer Therapy-induced Bonsupporting
confidence: 61%
“…These trials evaluated whether upfront ZA administration for patients starting AI therapy would lead to BMD preservation and reduced fracture incidence, compared with delayed ZA administration (i.e., after T-score fell below −2.0 or fracture was sustained). An improvement in BMD was observed in patients receiving early ZA, though reduction in fracture risk was not seen in the studies assessing this endpoint [11][12][13]. The absence of fracture risk reduction has made routine early administration of ZA a controversial practice.…”
Section: Discussionmentioning
confidence: 91%
“…Further, ZA has been shown to directly inhibit breast cancer cell invasion in a dose-dependent manner, making it a natural choice in postmenopausal women with a history of breast cancer who are at risk for ongoing bone loss. A North Central Cancer Treatment Group (N03CC) trial and the Zometa-Femara Adjuvant Synergy sister trials (Z-FAST, ZO-FAST, and E-ZO-FAST) were designed to investigate whether ZA would be effective for prevention of bone loss and fractures in postmenopausal women without osteopenia or osteoporosis (i.e., T-score ≥−2.0) [11][12][13][14]. These trials evaluated whether upfront ZA administration for patients starting AI therapy would lead to BMD preservation and reduced fracture incidence, compared with delayed ZA administration (i.e., after T-score fell below −2.0 or fracture was sustained).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the completed trials investigated adjuvant bisphosphonate therapy for its effect on bone health [7][8][9][10][11][12] . Those trials often compared early with delayed bisphosphonate therapy rather than adjuvant za with no bisphosphonate, or considered primary endpoints that were unrelated to breast cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%